Fazer sentido para fazer sentir: ressignificações de um corpo negro nas práticas artísticas contemporâneas afro-brasileiras - Lima, Diane Sousa da Silva (2017)
This research analyzes the effects of sense of a set of Afro-Brazilian contemporary works and artistic practices from the discursive mechanisms of enunciation that configure the regime of meaning, interaction and risk. Analyzing a corpus formed by a set of practices and actions that intervene in urban, media and institutional spaces, taking as a temporal cut the beginning of the 21st century to the present day, it aims to understand how this black body by means of enunciative mechanisms of its choices aesthetic arrangements of plasticity, figurativeness and thematization of a set of works. By discursively recombining the arrangements, they construct new narratives, new senses endowed with criticality that we aim to show, collaborate for the deconstruction of racial stereotypes. The central hypothesis of the research is that the fact that a target blackbody becomes an enunciator, enjoying its own faculty of the human condition of giving meaning to the world, is able through artistic practices to create ruptures that contribute to make the racial stereotypes of the country. The second hypothesis is that these practices, by creating interventions in the media, urban and institutional spaces, break the regimes of invisibility that, under the effect of structural racism, operate in the official circuits and legitimating national cultural production. When accessing a memory of the body, the third hypothesis proposes that these practices actualize in an ancestral knowledge, resignifying the social imaginary, encompassing new ways of doing and aesthetic possibilities. Using as a framework the semiotics of Algirdas Julien Greimas, the semiotics of the social of Eric Landowski and the contributions to the plastic semiotics of Ana Claudia de Oliveira, we verified that through the transitivity of enunciating, the set of works analyzed show that there were significant ruptures in the visibility schemes in support of a process of re-signification that is under way; also, that by being an act of resistance, they actualize in the present, an ancestral and mythical memory that keeps connected different times and spaces. Still, producing affections and intervening in the media, urban and institutional spaces, we saw that before the structure of the racial program, the practices are still focused and restricted, limiting their communication amplitude. At the end, we find that the aesthetic possibilities that we inaugurate point us to a future of learning where more investment in aestheticity and strategies of visibility are essential to potentiate their senses being sensed